Spark plasma sintered hydroxyapatite / bioglass composite for improved biological performance / Muhammad Rizwan - Muhammad , Rizwan (2019)
The most common biomaterials employed in orthopaedic and dental surgery are calcium phosphate (CaP) based, such as hydroxyapatite (HA) and β-tricalcium phosphate (TCP). Although HA exhibits tremendous biocompatibility, its close resemblance with the mineralized phase of natural bone affects the bioresorption rate in the body. Furthermore, the in vitro reactivity of HA is insufficient, and several in vivo studies confirmed the inadequate development of osseous tissues. Several attempts were made to combine HA with bioactive glasses, with the aim to obtain composite materials with improved bioactivity, controllable resorption rate and enhanced osseointegration. However, the high-temperature treatments required to sinter HA-based composites causes the bioactive glass to crystallize into a glass–ceramic and/ or react excessively with HA, exhibiting possible negative effects on its bioactivity, resorption and osseointegration. In this study, Bioglass®45S5 (BG) has been added into the HA matrix. BG exhibits the highest bioactivity (IB>8) among all bioceramics and forms very strong bonds with the surrounding tissues. Composite scaffolds containing BG powder (0 to 30 wt %) and BG fibers (0-20 wt %) were prepared using Spark Plasma Sintering (SPS) and conventional sintering. The SPS simultaneously compacts and sinters at relatively less severe processing conditions (compared to the conventional route), yielding novel findings related to the ability to prevent glass devitrification and excessive reactions between the constituents. The avoidance of excessive reactions and devitrification is critical, as the unique characteristics of BG (high bioactivity and extremely high osseointegration) and HA (similarity with the mineralized phase of natural bone) are lost or significantly deteriorated as a result of excessive reaction and devitrification. XRD analysis confirmed the absence of any crystalline phase (other than HA and β-TCP) resulting from the excessive reaction between HA and BG in SPSed scaffolds. On the other hand, the conventionally processed composites are composed of the β-TCP, Rhenanite and glassy phases. FESEM and EDAX analysis confirmed the presence of glassy phase with rounded morphology in the SPSed samples, which changed to a longer shape resembling the fibrous morphology when the BG fibers were used as reinforcement. Bulk density analysis of the composites was conducted using the Archimedes’ principle. Microhardness indentation was used to evaluate the hardness of each phase in the samples. The in vitro bioactivity analysis of the composite samples by immersion in simulated body fluid (SBF) showed enhanced bioactivity of the composite samples with higher BG content. The formation of biomimetic carbonated HA (CHA) on the composite samples has been confirmed by FESEM, EDAX and FTIR analysis. The in vitro resorption behavior was analyzed by immersion of the samples in Tris solution. The in vitro biological behavior of SPSed composite samples was evaluated in human bone marrow derived mesenchymal stromal cells (hBMSCs). The in vitro hBMSCs attachment (using SEM), mineralization (using EDAX) and proliferation (using Alamar blue staining) were evaluated initially. In next stage, the osteogenic differentiation (evaluating BMP-2, collagen I and Osterix formation) was analyzed by confocal laser scanning microscopy (CLSM). The SPSed HA-BG samples showed improved in vitro biological performance with higher BG content (particularly containing 30 wt % BG).